PHYTOREMEDIATION OF MERCURY CONTAMINATED SOILS IN A SMALL SCALE ARTISANAL GOLD MINING REGION OF INDONESIA - Kokyo Oh; Sachiko Takahi; Sri Wedhastri; Hardita Librasanti Sudarmawan; Retno Rosariastuti; Irfan Dwidya Prijambada (International Journal of Biosciences and Biotechnology, 2015)
In the small gold mining regions of Indonesia, the tailings or waste water containing mercury commonly may be released into agricultural lands resultimg soil contamination. Phytoremediation is a low-cost and environmental friendly alternative to traditional techniques such as soil heating, soil removal, and soil washing. In this study, a sweet sorghum combined with the inoculation of a rhizobacteria, Agrobacterium tumefaciens, was tested in a field experiment with mercury contaminated soil from a small scale gold mining. Plant growth, uptake and accumulation of mercury by the sweet sorghum, and effects of the Agrobacterium tumefaciens inoculation on mercury accumulation were investigated. The average of mercury content in the soil was 3.76 mg/kg. The results showed that the sorghum grew well, and the inoculation of Agrobacterium tumefaciens promoted the plant growth, but did not increased the mercury concentration in both root and stem parts of the sorghum. The accumulation of mercury was 6.2?/plant for sorghum without Agrobacterium tumefaciens, and 14.0?/plant for sorghum with Agrobacterium tumefaciens. It was estimated that the phytoremediation efficiency of mercury was 414 and 934 mg/ha for sweet sorghum without Agrobacterium tumefaciens inoculation and with Agrobacterium tumefaciens inoculation, respectively.